2018
DOI: 10.1007/s00264-018-4138-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for hallux valgus: a systematic review of current surgical techniques.

Abstract: The studies included were of too little level of evidence to allow for data pooling or meta-analysis. There were too few studies on each surgical technique category to assess whether one is more effective than the rest. However, there is some evidence that the Chevron and Akin showed the most potential for improvement of the HVA and the Endolog for the IMA. An overall complication rate of 13% was obtained among all included studies. Appropriately powered randomized controlled trials, utilizing validated outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 40 publications
4
67
0
1
Order By: Relevance
“…The Reverdin-Isham technique was reported to vary from a 5% [24] to a 73% [25] rate of complications. The Endolog technique was reported to have a range from 0 to 10% complication rates and in the distal soft tissue release group from 0 to 4% of cases [12]. During the third-generation technical literatures, the rate of complication was also varied from a 24% [11] or 15.5% [7] or 14% [14] or 10% [16] or 2% [15].…”
Section: Clinical Outcomes Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reverdin-Isham technique was reported to vary from a 5% [24] to a 73% [25] rate of complications. The Endolog technique was reported to have a range from 0 to 10% complication rates and in the distal soft tissue release group from 0 to 4% of cases [12]. During the third-generation technical literatures, the rate of complication was also varied from a 24% [11] or 15.5% [7] or 14% [14] or 10% [16] or 2% [15].…”
Section: Clinical Outcomes Clinicalmentioning
confidence: 99%
“…To date, many studies have evaluated the results of MIS techniques and open therapeutic surgeries for hallux valgus [8,11]. Meanwhile, systematic reviews have been reported to estimate the results of MIS techniques for treating the hallux valgus [1,12]. Those reviews pinpointed limitations of the achievable evidence to determine clear proposals for MIS in hallux valgus correction.…”
Section: Introductionmentioning
confidence: 99%
“…A promising procedure that combines the advantages of a minimally invasive surgery with the corrective power of metatarsal osteotomies is the Minimally Invasive Chevron-Akin (MICA) technique. It consists of a distal soft tissue release, an Akin phalangeal osteotomy and an extracapsular, distal, chevron osteotomy of the first metatarsal fixed with compression screws [46,47].…”
Section: Minimally Invasive and Novel Proceduresmentioning
confidence: 99%
“…[5] However, the reported outcomes of these procedures have varied. [1,[6][7][8][9] Among these techniques, the minimally invasive chevron and akin (MICA) procedure, which was described primarily by Vernois and Redfern, [9] has become widely used. The main advantage of this procedure is that it is extraarticular, which probably reduces the incidence of postoperative complications affecting range of motion and plantar exion power.…”
Section: Introductionmentioning
confidence: 99%